2017
DOI: 10.1177/1420326x16687800
|View full text |Cite
|
Sign up to set email alerts
|

A new empirical approach for predicting heat strain in workers exposed to hot indoor environments

Abstract: There is still a great need for a comprehensive index that could fully describe heat stress and, at the same time, provides a reliable correlation with the physiological responses of the human body. Using artificial neural networks, this study aims to present a new empirical model for predicting heat strain based on body core temperature in workers exposed to hot indoor environments. The study group consisted of 165 male workers working in heat treatment processes of metal industries in the central Iran. A pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…are common examples of heat-related illnesses induced by hot workplaces. 6 When exposed to hot environments for an extended period, the kidneys of such workers are affected largely. 7 Several of the most recent studies show the role of the environment of underground places on heat exposure on their workers.…”
Section: Introductionmentioning
confidence: 99%
“…are common examples of heat-related illnesses induced by hot workplaces. 6 When exposed to hot environments for an extended period, the kidneys of such workers are affected largely. 7 Several of the most recent studies show the role of the environment of underground places on heat exposure on their workers.…”
Section: Introductionmentioning
confidence: 99%
“…13 A hot environment often results in heat stress, health symptoms and reduced productivity for people who are exposed to it. 47 Therefore, in recent years, many researchers have focused on heat-related problems caused by the hot environment in naturally ventilated buildings. 8–13…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A hot environment often results in heat stress, health symptoms and reduced productivity for people who are exposed to it. [4][5][6][7] Therefore, in recent years, many researchers have focused on heat-related problems caused by the hot environment in naturally ventilated buildings. [8][9][10][11][12][13] Generally, indoor hot environment means high temperature (above 32 C) and high relative humidity (above 60%).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The hot environments greatly influence workers' health and working efficiency. [4][5][6] Aliabadi et al 7 found that the dry bulb temperature was the most important factor that affects the human heat strain. Heat stroke occurrence, for example, increases exponentially at high temperature.…”
Section: Introductionmentioning
confidence: 99%